From Imagination to Expression: Exploring Students’ Narrative Experiences of AI-Integrated Poetry Writing Through the Anchor Eyes Learning Model in Sumenep Junior High Schools - Isma’il Isma’il; Atok Miftachul Hudha; Daroe Iswatiningsih; Ly Aminas (International Journal of Educational Narratives, 2026)
Background. The rapid development of digital technology and artificial intelligence (AI) has transformed educational practices by creating new opportunities for creative and student-centered learning. In poetry writing, however, many junior high school students continue to experience difficulties in generating ideas, developing imagination, selecting appropriate diction, and expressing creative thoughts. These challenges indicate the need for an innovative instructional model that integrates students’ creative processes with AI-assisted learning. Purpose. This study aims to explore how the AI-assisted Anchor Eyes Learning Model improves junior high school students’ poetry writing skills by addressing the learning barriers they encounter during the creative writing process. Method. This study employed a descriptive qualitative design involving 70 eighth- and ninth-grade students from four junior high school classes in Sumenep Regency. Data were collected through classroom observations, reflective interviews with teachers and students, analysis of students’ poetry manuscripts before and after the implementation of the model, and supporting documentation. The data were analyzed using the Miles and Huberman interactive model, consisting of data collection, data reduction, data display, and conclusion drawing with triangulation and member checking to ensure trustworthiness. Results. The findings reveal that the AI-assisted Anchor Eyes Learning Model substantially enhanced students’ poetry writing by improving their ability to generate ideas, develop imaginative expression, select more appropriate diction, employ richer figurative language, and organize poetic structures more effectively. Reflective learning supported by AI tools also reduced students’ creative blocks, increased learning motivation, and enabled teachers to facilitate a more interactive and personalized writing process. Approximately 85% of teachers and students were already familiar with digital learning devices, facilitating the integration of AI into classroom activities. Conclusion. The AI-assisted Anchor Eyes Learning Model provides an effective pedagogical approach for improving poetry writing skills by transforming students’ creative writing processes while overcoming common obstacles in idea generation, language development, and creative expression.